2023
DOI: 10.1021/acsnano.2c12314
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Engineering on Plasmonic Nanostructures for Efficient Photocatalysis

Abstract: Plasmonic nanostructures have shown immense potential in photocatalysis because of their distinct photochemical properties associated with tunable photoresponses and strong light−matter interactions. The introduction of highly active sites is essential to fully exploit the potential of plasmonic nanostructures in photocatalysis, considering the inferior intrinsic activities of typical plasmonic metals. This review focuses on active site-engineered plasmonic nanostructures with enhanced photocatalytic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 376 publications
0
38
0
Order By: Relevance
“…[37][38][39] Another fascinating optical property of plasmonic metal nanocrystals is their shape-and size-dependent LSPR, which contributed to the signal enhancement of surface enhanced Raman spectroscopy (SERS). 40,41 When the surface of the plasmonic nanocrystal is covered by a shell made of catalytic metal, SERS offers a way to achieve in situ monitoring of chemical reactions. Fig.…”
Section: Opportunities: Two Is Better Than Onementioning
confidence: 99%
“…[37][38][39] Another fascinating optical property of plasmonic metal nanocrystals is their shape-and size-dependent LSPR, which contributed to the signal enhancement of surface enhanced Raman spectroscopy (SERS). 40,41 When the surface of the plasmonic nanocrystal is covered by a shell made of catalytic metal, SERS offers a way to achieve in situ monitoring of chemical reactions. Fig.…”
Section: Opportunities: Two Is Better Than Onementioning
confidence: 99%
“…Plasmonics enables metal NPs to act as antennas, capturing light from around the particle with an optical cross section that is orders of magnitude larger than the physical size of the particle. The strong localization of incident light makes plasmonics ideal for enhancing photoconversion in photovoltaics, 55 PC, 56 and light‐emitting devices 57 …”
Section: Unconventional Strategiesmentioning
confidence: 99%
“…Fortunately, plasmonic metal-based photocatalysts provide precious opportunities to solve the above challenges. Owing to the localized surface plasmon resonance (LSPR) effect induced by plasmonic metals (e.g., Au, Ag, Ni, and Cu), plasmonic metal-based photocatalysts have attracted increasing attention recently. The good light harvesting ability, high charge separation efficiency, and strong capacity of activating reactants in a plasmonic metal-based photocatalyst consequently cause a good photocatalytic performance. For instance, some studies explored the enhancement roles of many plasmonic noble-metals on common supports like SiO 2 and Al 2 O 3 in CO 2 reductions. , And they confirmed that due to the strong light absorption ability, the CO 2 reduction process could be initiated under mild conditions. Besides, a series of conventional semiconductors involving TiO 2 , g-C 3 N 4 , and GaN has also been combined with plasmonic metals so that the charge transfer efficiency in plasmonic metal/semiconductor systems could be improved due to the local electric field induced by LSPR effect, increasing the photocatalytic activity. Recently, some research investigated bimetallic catalysts with two plasmonic metals. Owing to the synergistic effect between plasmonic metals, the LSPR effect could be enhanced, further leading to highly efficient photocatalytic CO 2 reduction reactions.…”
Section: Introductionmentioning
confidence: 99%